Enhancement of the electrocatalytic activity of phthalocyanines through the reduction in symmetry and conjugation to detonation nanodiamonds - Ncwane, Lunathi (Rhodes University, Faculty of Science, Department of Chemistry)
This thesis reports on the synthesis of novel phthalocynines tetrakis[(benzo[d]thiazol-2ylthio)phthalocyaninato]cobalt(II)chloride (complex 1) and tris(2-(ethylthio)benzo[d]thiazole)2-(phthalocyanine-9-ylthio)propionate cobalt(II) chloride (complex 2). The complexes are combined with DNDs via different techniques such as Ï€-Ï€ stacking, covalent linkage and sequential modification on glassy carbon electrode. The synthesized MPcs and conjugates were characterized using UV-visible, mass, Fourier transform infrared, and Raman spectroscopies as well as transmission electron microscopy and dynamic light scattering. Combining MPcs with DNDs sought to improve electrooxidation of hydrazine. The electrochemical studies were conducted using cyclic voltammetry, chronocoloumetry, electrochemical impedance spectroscopy and chronoamperometry. Hydrazine was utilized as an analyte of interest, due to its mutagenic and carcinogenic effects. Glassy carbon electrodes (GCE) were modified using drop and dry method. The conjugation via covalent linkage proved to be the best way of enhancing electrocatalytic properties. Since it performed better in terms of limit of detection (0.33 Î¼M), even though catalytic rate and sensitivity are not the highest.
Keywords: Phthalocyanines; Electrocatalysis; Nanodiamonds; Hydrazine